2007
DOI: 10.1124/dmd.106.013722
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Novel DefectiveCYP2C9*24Allele

Abstract: ABSTRACT:CYP2C9 is one of the major drug-metabolizing enzymes, and it is involved in the oxidative metabolism of approximately 10% of clinically important drugs, among which some, such as the anticoagulant warfarin, have a narrow therapeutic index. The human CYP2C9 gene is highly polymorphic. We found a new sequence variation in exon 7 of the CYP2C9 gene (1060G>A) resulting in a substitution of acidic amino acid glutamate to basic lysine (E354K) when translated. The allele, designated CYP2C9*24, was present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In insect microsomes, relatively lower expressed proteins could be detected for variant CYP2C9.36 when compared with which in COS-7 cells. Herman et al reported a similar phenomenon for the CYP2C9.24 variant [16] . As Maekawa et al proposed, this discrepancy might be because of the different degradation rates of improperly folded proteins in insect and mammalian cell expression systems [8] .…”
Section: Discussionmentioning
confidence: 64%
“…In insect microsomes, relatively lower expressed proteins could be detected for variant CYP2C9.36 when compared with which in COS-7 cells. Herman et al reported a similar phenomenon for the CYP2C9.24 variant [16] . As Maekawa et al proposed, this discrepancy might be because of the different degradation rates of improperly folded proteins in insect and mammalian cell expression systems [8] .…”
Section: Discussionmentioning
confidence: 64%
“…Guo et al (2005a) reported that the protein expression level of CYP2C9.13 was 39% of that of CYP2C9.1 in the COS-1 expression system by Western blotting. The discrepancy in total protein levels between their study and ours might be due to different rates of degradation of improperly folded proteins between the two expression systems, as observed for CYP2C9.24 between yeast and mammalian systems (Herman et al, 2007). The mammalian cell system seems to be more relevant to assess the potential effects of CYP2C9*13 on its protein expression in vivo although accurate estimation of its holoprotein levels might be difficult in this system because of the low expression levels.…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that in vitro results can give a reliable indication of the in vivo effect of a specific variant (35,36). Both the neural network predictions, which are in silico predictions based on in vivo data, and the in vitro results showed the same impact (decreased, normal, or increased activity) of the investigated variants.…”
Section: Discussionmentioning
confidence: 90%
“…4A). To confirm the contributions predicted by the model, four variants and the *2 allele were expressed in HEK (human embryonic kidney) 293 cells, which are completely devoid of any other metabolic enzymes (35,36), and incubated with bufuralol (table S2). The direction of our predictions (decrease or increase) was in concordance with the in vitro results, with accuracy increasing as the variant frequency increases.…”
Section: In Vitro Validation Of Predicted Variant Contributionsmentioning
confidence: 99%